Mensuração de ativos biológicos (aves e suínos): uma análise crítica do CPC-29 ativo biológico e produto agrícola - Nascimento, Renata Bandeira Gomes do (2011)
The purpose of this study was to determine whether the adoption of fair value as a measurement method of biological assets, specifically poultry and pigs, as required by IAS-41 and CPC-29, is more appropriate than the cost of acquisition and/or formation within the reality of the Brazilian market through: (1) confirmation of the existence of an active market, (2) measurement of these assets at fair value highlighting the strengths and weaknesses of the methodology, (3) comparison between the values measured through the historical cost and fair value, (4) identification of the appropriated method to measure biological assets for production, and (5) analysis of the improvement or not of the comparability of financial statements of companies in the poultry, pork and beef agribusiness, after the adoption of IAS-41 and CPC-29. In order to achieve such objectives an exploratory research was developed, in which the data was collected through literature research, interviews, observation and document analysis. According to its representation in the agribusiness sector, BRF Brasil S.A. was chosen to be analyzed as experimental study case. The results of the analyzed data were: (1) that there is no active market for poultry and pork in Brazil, (2) that the method of fair value measurement requires the adoption of biased assumption regarding the allocation of the profit margin to the agriculture activity and subjective assumption related to the discount rate for the biological assets within the scope of this study, (3) that specifically, as a result of BRF s experimental study case, the difference between historical cost and market value is not material, (4) that the adoption of fair value as a method of measurement of biological assets for production causes distortion in the financial statements, and (5) comparability of financial statements was impaired after the adoption of IAS-41 and CPC-29. Hopefully, the results achieved will contribute to market professionals, academics, legislators and non-government authorities in improving the quality of financial statements.